Airway inflammation in children and adolescents with bronchiolitis obliterans. Issue 1 (May 2015) - Rosewich, Martin; Zissler, Ulrich M.; Kheiri, Tanja; Voss, Sandra; Eickmeier, Olaf; Schulze, Johannes; Herrmann, Eva; Dücker, Ruth Pia; Schubert, Ralf; Zielen, Stefan
Highlights First sputum analysis from patients with BO originating in childhood. Monitoring of bronchial inflammation from induced sputum. Analysis of sputum samples by cell count, qRT-PCR and CBA.